(3YUGI GdWhSi hgh GdCSWQdGH GdNWis - (3GdeXaQ Hf eMeO, TQa GdOjf GdWhSj,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdPi JhMO HGdYR hGdHbGA hHYO hEfi cfJ eOI ai GSJNQGL gPg GdBdI GdTQjaI GdbSe GdChd ai GdYed s
(3BNQgG (B:s
(3hdChd GdLhRGA fbWJGf hdSGFQ CbSGeg fbWI fbWI hdChd GdSQWGf KdGK fbW hbO JeJ hPdc eG CQOfG Cf fHjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B86(3C (B- (3U(B104(3Hs
(3HBNQgG LOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(5479or) s
Keywords: (3Gdadcs